1966
DOI: 10.1152/ajplegacy.1966.211.3.667
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of myocardial developed tension and its relation to oxygen consumption

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

1968
1968
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(30 citation statements)
references
References 0 publications
0
29
0
1
Order By: Relevance
“…Shortly thereafter, Evans and Matsuoka (2) concluded from studies on the dog heart-lung preparation.that "there is a relation between the tension set up on contraction and the metabolism of the contractile tissue." These demonstrations, that tension 2 development is an important determinant of MVo2, have been verified repeatedly (3)(4)(5)(6)(7)(8). It has also been proposed that the heart's oxygen utilization is determined primarily by a closely related variable, the work performed by the contractile elements (CEW) (9).…”
Section: Introductionmentioning
confidence: 78%
“…Shortly thereafter, Evans and Matsuoka (2) concluded from studies on the dog heart-lung preparation.that "there is a relation between the tension set up on contraction and the metabolism of the contractile tissue." These demonstrations, that tension 2 development is an important determinant of MVo2, have been verified repeatedly (3)(4)(5)(6)(7)(8). It has also been proposed that the heart's oxygen utilization is determined primarily by a closely related variable, the work performed by the contractile elements (CEW) (9).…”
Section: Introductionmentioning
confidence: 78%
“…The presence of fully developed transmural gradients in lactate and creatine phosphate when flow was stopped for only 15 seconds and the significant changes found in all metabolites, including ATP, when flow was stopped for 30 seconds indicate that the metabolic changes in the myocardium were intimately related to the energy needs of the ventricle as regulated by the existing loading conditions. The significantly elevated ventricular end-diastolic and systolic pressures produced by volume loading undoubtedly resulted in a substantially increased wall stress, which is a primary determinant of the myocardial energy needs (31). The elevated enddiastolic pressure might be of particular significance if increasing ventricular filling pressure preferentially moves the inner region sarcomeres closer to the peak of their active length-tension curve, as suggested by Yoran et al (32).…”
Section: Discussionmentioning
confidence: 96%
“…The increased 2DG uptake into the heart muscle may also be interpreted in relation to oxygen consumption in this muscle. Previous studies reported that there existed high correlations between oxygen consumption and some parameters related to tension in the heart muscle (BRITMAN and LEVINE, 1964;MCDONALD et al, 1966;SARNOFF et al, 1958 ;SUGA et al, 1980;WEBER and JANICKI, 1977). Therefore, the large amount of 2DG uptake into the left ventricular wall may be considered to be correlated with a high tension developed in this muscle.…”
mentioning
confidence: 89%